Comment to "Revisionism and the dangers of deliberate lies from Hannah Arendt's perspective": Revisionism, Denialism and an Informational Approach to World Discourse - Matos, José Claudio (2022)
Commented article reference:  : PASSOS, F. A. O revisionismo e os perigos da mentira deliberada na perspectiva de Hannah Arendt. Trans/Form/Ação: revista de filosofia da Unesp, v. 44, n. 3, p. 115-134 2021.